2021
DOI: 10.3390/met11040582
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study and Experimental Validation of Deformation of <111> FCC CuAl Single Crystal Obtained by Additive Manufacturing

Abstract: The importance of taking into account directional solidification of grains formed during 3D printing is determined by a substantial influence of their crystallographic orientation on the mechanical properties of a loaded material. This issue is studied in the present study using molecular dynamics simulations. The compression of an FCC single crystal of aluminum bronze was performed along the <111> axis. A Ni single crystal, which is characterized by higher stacking fault energy (SFE) than aluminum bronz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Slip band patterns, mobile and sedentary configurations depend on the crystal's orientation and their shape. Some of them were traced on FCC metals [32,33] and aluminum bronze with the deformation axis orientation [111] [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Slip band patterns, mobile and sedentary configurations depend on the crystal's orientation and their shape. Some of them were traced on FCC metals [32,33] and aluminum bronze with the deformation axis orientation [111] [33].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the authors in their works [32,33] simulated uniaxial compression along <001> and <111> for FCC single crystals of materials using in AM, which showed the effect of stacking fault energy on their deformation behavior. Simulation also made it possible to identify the role of different types of dislocations in hardening and deformation.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most effective approaches to studying gradient materials is atomistic simulation. It provides detailed information on the generation and evolution of structural defects in single crystal and nanocrystalline metals and alloys [21][22][23][24][25]. For example, a molecular dynamics simulation of nanocrystalline copper showed that the strength of gradient samples correlates with the average grain size and obeys the direct and inverse Hall-Petch relation [26].…”
Section: Introductionmentioning
confidence: 99%